Aplikasi Ekoenzim Terhadap Pertumbuhan Tanaman Bayam Merah (Amaranthus Tricolor L.) Pada Sistem Hidroponik Rakit Apung - Rosi Widarawati; Budi Prakoso; Melinda Dian Sari (UM Purwokerto Press, 2023)
This research was conducted to determine the effect of ecoenzyme concentration on the growth of red spinach plants in a hydroponic floating raft system conducted at the Greenhouse of the Faculty of Agriculture, Jenderal Soedirman University, Purwokerto. Ecoenzyme application treatment, namely: 0 ppm; 1000 ppm; 2000 ppm; and 3000 ppm with 6 replications arranged based on Completely Randomized Block Design (RAKL). Observations made consisted of: plant height, number of leaves, root length, leaf area, and root volume. The F test (ANOVA) at an error level of 5% was carried out to find out whether the treatment affected the observed variables. The LSD test at an error level of 5% is carried out if the F test is real. The results showed that the plant height of red spinach 2 MST was not affected by differences in ecoenzyme concentrations in the nutrient media; Plant height at 4 WAP with 1000 ppm ecoenzyme treatment was the highest and plant height at 6 WAP with 0 ppm and 1000 ppm ecoenzyme treatment was not different, while plant height growth with 2000 ppm and 3000 ppm treatment was lower. The number of leaves at 2 WAP, 4 WAP and 6 WAP, root length, leaf area, and root volume in all treatments of ecoenzyme concentration application showed no difference.